澳門普通小學教師職業幸福感：: 現況、影響因素及提升策略 = THE OCCUPATIONAL WELL-BEING OF MACAU PRIMARY SCHOOL TEACHERS：CURRENT STATUS, INFLUENCING FACTORS, AND ENHANCEMENT STRATEGIES - 黎嘉穎 (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 教師; 澳門小學; 職業幸福感

Teacher's Teaching Style and the Learning Attitude of Elementary School Students: A Macau Case Study = 小學生學習態度與教師教學風格現況之研究—以澳門某小學為例 - 洪麗 (University of Saint Joseph, 2024)
Keywords: Learning Attitude; Macau; Primary School; Teacher's Teaching Style; Thesis and Dissertations Master of Education (MED); University of Saint Joseph

探討澳門普通小學教師在融合教育背景下的工作相關壓力及有效應對策略 =: Exploring Work-Related Stress and Effective Coping Strategies in the Context of Inclusive Education Among Mainstream Primary Teachers in Macau - 黃家敏 (University of Saint Joseph, 2024)
Since 2006, the Government of Macau has been promoting inclusive education. This has now been ongoing for seventeen years. As education policies gradually improve, the focus has shifted from students in inclusive settings to the realm of teachers. With an increasing number of inclusive students, the corresponding work pressures faced by teachers has also increased. The aims of this study are to better understand the work-related stress, sources of stress, and subsequent coping strategies used by mainstreamteachers within the inclusive education sector of Macau. This study used qualitative research methods, interviewing twelve frontline teachers from eight different private primary educational institutions. Eight of these teachers work in schools practicing inclusive education, while four were employed in regular schools. However, all twelve participating teachers had experience in teaching inclusive students but also lacked any specialized background in special education. Following and obtaining and meticulously analyzing interview data, supported by relevant literature, the study findings are presented as follows: 1. Views and Attitudes of Regular Teachers in Inclusive Schools towards Inclusive Education The interviewed teachers support the concept of inclusive education but were concerned about student behaviors and their learning challenges. These concerns included inappropriate behaviors, learning disabilities, and the teachers’ own pedagogical demands. In managing student behaviors, teachers found it difficult to handle the emotional control of inclusive students, leading to disruptions in class. Regarding learning, teachers had to use additional and extra time on after-class tutoring, increasing their workload. Teaching inclusive students also complicated the instruction, requiring teachers to undergo additional training and preparation. 2. Work-Related Stress and its Sources among Regular Teachers within Inclusive Schools The participating teachers rated their stress-resilience as not low, but rather they experienced medium to high levels of work-related stress, mainly due to long working hours and extensive workloads. The study identifies four main sources of stress: （i） The nature of work, including extensive teaching and non-teaching tasks, including heavy class management, or multiple roles. （ii） Social relationships, where regular teachers lacked an understanding of resource teachers’ roles, leading to ineffective communication and an underutilization of resource teachers in schools. （iii） Organizational structure, where schools involved in inclusive education required improvements in facilities and teaching environments, particularly in the safety of sports areas. Additionally, not all mainstream teachers had access to inclusive education resources, and the instructional adjustments for inclusive students did not fully meet their needs. （iv） Social aspects, where the public did not fully understand the concepts of inclusive education, and expectations on teachers were excessively high. Furthermore, teachers were dissatisfied with their salaries and benefits, which they felt were not commensurate with their heavy workload. The study also found that female teachers faced additional stress from both work and family responsibilities, as they also bear the burden of caring for and educating their own children at home. 3. Responses and Coping Methods of Regular Teachers in Inclusive Schools to Work-Related Stress The study analyzed the negative impacts of work-related stress on teachers’ physical health, psychological state, and behavior. The impacts included poor sleep quality or insomnia and emotional states of worry and anxiety. In response to stress, teachers engaged in communication and social activities, exercise and rest, and dietary adjustments. However, these stress-relief methods did not effectively address the root causes of the stress, making long-term stress management a crucial issue for teachers. Based on the findings regarding stress perceptions, sources, and coping methods, the researcher proposes recommendations for teachers, educational institutions, and relevant government departments, with an aim to support and aid future policymaking in the area of inclusive education in Macau
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 小學; 工作壓力; 應對策略; 普通教師; 融合教育

EXPLORING MACAU SECONDARY SCHOOL TEACHERS’ UNDERSTANDING, PROFESSIONAL SKILLS, AND CHALLENGES TO INCLUSIVE EDUCATION OF STUDENTS WITH DISABILITIES/SPECIAL EDUCATION NEEDS - Sin, Sam I. (University of Saint Joseph, 2024)
Quality inclusive education creates educational opportunities for all students to achieve enhanced educational outcomes, and the quality of inclusive teaching depends on teachers’ knowledge, skills, resources and school support. However, not all schools are implementing inclusive education well enough to cater to the learning needs of students with special educational needs. This phenomenological case study explored the perspectives and experiences of five teachers in one inclusive secondary school in Macau. An Interpretative Phenomenological Analysis (IPA) of the in-depth semi- structured interview data revealed four themes: varied conceptualisations of inclusive education, professional training in inclusive practice, professional knowledge and practice experiences, and challenges to implementing inclusive education. Generally, while the teachers demonstrated awareness and some understanding of inclusive education, they also expressed the need for more knowledge and skills to implement inclusive education effectively in their schools. Additionally, they referred to time pressure, workload and insufficient professional development as impeding their personal processes of evolving inclusive teaching in their school. Recommendations were made considering Booth and Ainscow's (2002) Index of Inclusion to enable effective development and practice of inclusive education in the Macau secondary school and extend this to other schools
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; students with special education needs; teachers' professional skills; teachers' understanding

澳門小學普通班教師實施融合教育的教學困擾與因應策略之研究 =: A STUDY ON TEACHING DIFFICULTIES AND RESPONSE STRATEGIES OF TEACHERS IMPLEMENTING INTEGRATED EDUCATION IN ORDINARY CLASSES OF PRIMARY SCHOOLS IN MACAO - Ng, Wa Seng (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 因應策略; 小學普通班教師; 教學策略; 澳門

Exploring the learning effectiveness under the "formative assessment" reform of non-tertiary education in Macao: A Case Study =探討澳門非高等教育改革「形成性評核」下的學習成效－個案研究 - 何愛琴 (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 個案研究; 學習成效; 形成性評核; 教育改革

基模教學對百分比問題之程序流暢程度的有效性研究 =: EFFECTIVENESS OF SCHEMA-BASED INSTRUCTION (SBI) ON PROCEDURAL FLUENCY WITH PERCENTAGES PROBLEMS - Zhou, Mingyan (University of Saint Joseph, 2024)
Research suggested that students struggle because of lacking understanding of basic concepts, formulas, and procedures in algebra, leading to inefficiency in logical thinking and problem-solving skills. (Julius et al., 2018; Jupri et al., 2021). Schemabased instruction (SBI) aims to enhance learning and problem-solving by activating and building upon students' prior knowledge structures, known as schemas (Powell et al., 2008). The common schemas include the total, difference, change, equal groups, comparison, ratios/proportions (Hughes & Cuevas, 2020). SBI has been found to be effective, particularly for students who struggle with mathematics word problems (Marshall, 2012; Hughes & Cuevas, 2020). Research related to SBI has not yet been conducted in Macau region. An early pre-test was administered by the researcher, thirty-one students were asked to solve 10 questions about percentages. The results showed that some students lacked the fundamental knowledge needed to investigate and explore the abstract ideas, patterns, and relationships in percentages problems. A daily schema-based instruction (SBI) as a part of an experimental intervention study was implemented, pre-test and post-tests were administered to investigate the effect of SBI on students' mathematical procedural fluency skills. Thirty-one students from the researcher’s class were invited to engaged in 40 minutes of daily SBI lessons for two weeks, 12 lessons in total. During each of the twelve 40-minute session, students practiced schemas to develop procedural fluency competencies, such as solid number sense and arithmetic operations, to solve percentages problems. Within-group descriptive and inferential statistics were adopted. The results indicated that after SBI, students can solve mathematical problems with greater procedural fluency. This research shares implications and provides suggestions regarding SBI and procedural fluency
Keywords: SBI; Thesis and Dissertations Master of Education (MED); University of Saint Joseph; mathematics; percentages problems; procedural fluency; schema-based instruction; secondary education

小學資源教師教學成效及影響因素之研究 =: A STUDY ON THE TEACHING EFFECTS AND INFLUENCING FACTORS OF PRIMARY SCHOOL RESOURCE TEACHERS - Lam, Iok Ian (University of Saint Joseph, 2024)
Keywords: Inclusive Education; Resource Teachers; Teaching Effects; Teaching and Learning Situation; Thesis and Dissertations Master of Education(MED); University of Saint Joseph

EXPLORING MUSLIM STUDENTS LIVED EXPERIENCES IN MACAU: A PHENOMENOLOGICAL APPROACH - Ho, Kit Ieng (University of Saint Joseph, 2024)
Muslim community is one of the minority groups in Macau SAR China. Muslims are an interesting group in terms of research because of its diversity in respect to language, nationality, social status, and education level. Groups of people migrate for various reasons such as religion, politics, economy, and education. Individuals experience the age in between nineteen and twenty-four, which fall in the category of youth. Studies of Muslim youths have gained more attention in scholarship, statistical data, and research. The study seeks to understand Muslim students’ life and the needs of this minority group and explores how Muslim students perceive Islam and their own ability to cope with school related cultural pressures through qualitative, phenomenological approach, and focuses on exploring the common experiences of Muslim students in this city. This study used a conceptual framework based on critical race theory (CRT). We use in-depth interviews of five Muslim youth, ages between 19 and 24, to investigate their school life experiences and Islamic practices. We also administered questionnaires and field note to understand their social mobility, social capital and to gain a deeper understanding of their daily lives. A thematic analysis of the interview data produced the following themes: 1) Social mobility; 2) Social capital Relationship with friends; 3) Discrimination and micro-aggressions; and 4) Religion Identity. The study found that the Muslim status of the participants did not have a significant impact on their school experience, as they were able to find accommodation in their practice of religion and school life. However, the multiple identities of the participants as Macau citizens and their ethnic backgrounds did affect their social capital and sense of belonging. The study also examined the experiences of the participants within Macau society, including social factors such as racism. The results indicated that language and ethnicity were factors that hindered their integration into the community. In addition to the original themes, the analysis of the participants' stories in this research revealed two counter-narratives that challenge prevailing narratives. These counter-narratives include the deconstruction of oppressed Muslim women's narratives and the influence of local mainstream religious schooling on Muslim students' religious loyalty. These alternative narratives provide new insights into the lives of Muslim youths and challenge conventional stories. The findings of this study have important implications for educators, academics, and members of both Muslim and non-Muslim communities. By allowing youth to establish broader connections with society and increasing their motivation to participate in and contribute to the community, this study highlights the need for inclusive educational environments that support the diverse identities of students. Furthermore, the study provides young Muslims with a voice in society, empowering them to challenge dominant narratives and promote counter narratives that reflect their experiences and perspectives to meet critical race theory ethos of ongoing active struggle
Keywords: Critical Race Theory; Muslim youth; School experience; Thesis and Dissertations Master of Education (MED); University of Saint Joseph

「融合教育下澳門小學普通班教師班級經營面對的困難及可行策略之研究」 =: "A Study on the Difficulties Faced by Macau Primary School General Education Classroom Teachers in Class Management and Possible Strategies" - LEI, WENG KIT (University of Saint Joseph, 2024)
Keywords: Class Management; Inclusive Education; Macau Primary Schools; Qualitative Research; Teacher Attitudes; Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 教師態度; 澳門小學; 班級經營; 融合教育; 質性研究

THE LIFE DILEMMA AND ADJUSTMENT OF PARENTS OF CHILDREN WITH AUTISM SPECTRUM DISORDER IN MACAO =: 澳門自閉症類群障礙幼童的家長生活困境與調適 - Ieong, I. Teng (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 困境; 特殊教育; 自閉症兒童家長; 調適

小學聽覺障礙學生的融合教育現狀： 以澳門C學校為例 =: CURRENT STATUS OF INTEGRATED EDUCATION FOR STUDENTS WITH HEARING IMPAIRMENT IN PRIMARY SCHOOLS: TAKE MACAU SCHOOL C AS AN EXAMPLE - LIO, I TENG (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 支援服務; 澳門; 聽障學生; 融合教育

澳門教師的情緒智力、幸福感與教學效能之相關研究 =: AN EXPLORATORY STUDY ON THE RELATIONSHIP OF MACAU TEACHERS’ EMOTIONAL INTELLIGENCE, SENSE OF WELL-BEING AND TEACHER SELF-EFFICACY - Wong, Pou I. (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 幸褔感; 情緒智力; 教學效能

澳門教師自我效能感、集體效能感與融合教育態度之相關研究 =: A STUDY ON THE CORRELATION BETWEEN TEACHERS’ SELF-EFFICACY, COLLECTIVE EFFICACY AND ATTITUDES TOWARDS INCLUSIVE EDUCATION IN MACAO - Lei, Man Teng (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 教師自我效能感; 教師集體效能感; 融合教育態度

澳門小學教師對融合教育態度之研究 =: A Study on Macao Primary School Teachers ’Attitudes towards Inclusive Education - Kwok, Siu Kam (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 小學教師; 澳門; 融合教育

EXPLORING THE RELATIONSHIP BETWEEN WRITTEN COMMUNICATION COMPETENCE AND CULTURAL INTELLIGENCE (CQ): A CASE STUDY OF EFL LEARNERS IN MACAO - Sin, Man Teng (University of Saint Joseph, 2024)
Although Macau students received years of English lectures as compulsory, the outcome could be more favorable when applied to English written performance. In that written communication requires the individual to consider audience perception of the message, a challenge for ESL writers, this study explores whether different forms of feedback can enhance one’s cultural intelligence.The current study looked into the effect of incorporating peer involvement and instructor feedback in written communication, gaining insight into cultural nuances. In order to attain the objective, data were gathered through the utilization of an action research methodology employing a mixed-method design. Grade twelve local students attended a six-week six-week intervention consisting of two cycles. The focus of the intervention nurtured essay writing; the topics of which were inspired by popular musical lyrics, and involved a drafting process that incorporated feedback both from peer editing and the instructor.. The data collected throughout the study involved analysis of written samples (scores of draft and final version) using a paired samples t-test. In addition, students completed a pre-test and post-test survey of the cultural intelligence instrument (CQ), which measured their performance across four domains. There were statistically significant differences between cognitive CQ and motivational CQ between the scores attained before and directly after the intervention.. This study's findings suggest that the written communication of ESL students may be enhanced by adjusting . These findings enriched our understanding of how peer editing and teacher feedback with songs affected the outcomes of second language learners
Keywords: Music; Thesis and Dissertations Master of Education (MED); University of Saint Joseph; cultural intelligence; foreign language anxiety; writing competence

澳門融合教育小學資源教師的工作困難與需求 =: INCLUSIVE EDUCATION IN MACAO’S PRIMARY SCHOOL：THE WORK DIFFICULTIES AND NEEDS OF PRIMARY RESOURCE TEACHER - Chong, Hei Tong (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 小學資源教師; 工作困難; 融合教育

初任教師在融合教育中教學困擾及因應策略: 以澳門某三所私立學校的初任教師為例 = TEACHING CHALLENGES OF NOVICE TEACHERS AND COPING STRATEGIES IN INCLUSIVE EDUCATION: A STUDY OF NOVICE TEACHERS IN THREE PRIVATE SCHOOLS IN MACAO - Wong, Man U. (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 初任教師; 因應策略; 教學困擾; 融合教育

EDUCATORS' PERSPECTIVE OF STUDENTS WITH SPECIAL EDUCATIONAL NEEDS (SEN) AND THEIR SENSE OF BELONGING, SELF-COMPETENCE, AND AGENCY - Carvalho, Edna Line Henriques de (University of Saint Joseph, 2024)
What strategies did educators use to cultivate a sense of belonging, self-competence, and agency among students with Special Educational Needs (SEN)? Did educators face any challenges in implementing these strategies? Were the findings of this study specific to the inclusive school in Macau, or can they be generalised to other educational settings? This study brings to light educators' inner perspective of students' sense of belonging, self-competence, and agency. Specifically, it aims to uncover the academic and emotional needs of students with SEN and the importance that these may have in promoting a positive educational experience. By gathering the perspectives of educators in an inclusive school in Macau who work side-by-side with these students daily, we can understand how essential these elements are in contributing to their overall development. The purposive sampling approach was used in this study to further investigate various experiences and perspectives of educators within an inclusive classroom setting. The educators interviewed provided insight into an inclusive classroom with students with SEN in full-time attendance. The educators sampled in this study facilitated the search for strategies, challenges and support systems to cultivate a sense of belonging, self-competence and agency, among students with SEN. Findings showed educators' understanding of the importance of students with SEN's sense of belonging, self-competence and agency. The educators' awareness of their students' interactions with peers, and the educators themselves, was prominent, revealing how the sense of belonging for students with SEN affected these relationships. Regarding students' sense of self-competence, according to educators, students with SEN had opportunities to showcase their confidence in specific classroom areas and to exercise independence in the classroom, within the set curriculum and lesson plans. In the findings, educators illuminated the importance of agency in students with SEN. However, they were apprehensive about changes in lesson plans, cultivating a fully independent classroom setting and providing choices to students with and without SEN. The study's implications highlight the educational practices and policies that effectively supplement students with SEN's academic and social environments. The findings of this study aim to guide curriculum developers, educators and parental figures in fostering positive learning experiences for students with diverse learning needs
Keywords: Heutagogy; SEN; Self-competence; Students' agency; Thesis and Dissertations Master of Education (MED); University of Saint Joseph

EXPLORING COOPERATIVE LEARNING IN PROMOTING EQUITY, INCLUSION, AND COLLABORATION IN INCLUSIVE CLASSROOMS: A CASE STUDY - Loi, Man Hong (University of Saint Joseph, 2024)
This study presents a case study that explores teachers’ perspectives on the role of cooperative learning as a pedagogical approach in promoting equity, inclusion, and collaboration within inclusive classrooms. Additionally, it identifies both the perceived benefits and challenges associated with its application. The researcher sought data from primary school teachers in one inclusive school in Macau and employed in-depth semi-structured interviews. Twelve participants were involved in this qualitative study. The findings underscore the significant impact of cooperative learning in creating inclusive, engaging, and equitable educational environments, particularly for students with special educational needs. Overall, the participants viewed cooperative learning as a valuable pedagogical approach that fosters equity, interaction, student engagement, and collaboration in inclusive classroom settings. While cooperative learning presents several benefits in promoting an inclusive and equitable learning environment, the findings also reveal unique challenges that require careful management and adaptation by teachers. Some of these challenges include certain students dominating group work, difficulties in integrating students with different disabilities, and time management issues for effective cooperative learning implementation. Overall, the case study contributes valuable insights into to the complex dynamics of cooperative learning in mixed ability classes
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; cooperative learning; inclusion; inclusive education; inclusive practice